Developing Sensitivity to Subword Combinatorial Orthographic Regularity (SCORe): A Two-Process Framework. (3rd May 2016) - Mano, Quintino R.
ABSTRACT: Accumulating evidence suggests that literacy acquisition involves developing sensitivity to the statistical regularities of the textual environment. To organize accumulating evidence and help guide future inquiry, this article integrates data from disparate fields of study and formalizes a new two-process framework for developing sensitivity to subword combinatorial orthographic regularity (SCORe). This framework posits that sensitivity to SCORe emerges from task-driven attentional control enabling and being modulated by incidental statistical learning. The first section of this artilce defines SCORe and reviews evidence for sensitivity to SCORe among children. The second section discusses incidental statistical learning (i.e., chunking, statistical computations), task-driven attentional control (i.e., afferent modulation), and their bidirectional interplay in SCORe learning. The third section brings basic knowledge about the neurobiology of orthographic processing to bear on the development of SCORe sensitivity. This article concludes with areas of future inquiry related to reading instruction and developmental dyslexia.